MANAJEMEN KURIKULUM LEMBAGA PENDIDIKAN ISLAM DI ERA DIGITAL: TANTANGAN TRANSFORMASI DAN INOVASI PEMBELAJARAN - Muhammad Afrijaludin; Fadhila Najah Annisa; Syahidah Salsabila; Puja Maharani; Syifa Fajriyah; Girllis Nurrukhyati Ramdanis Sadiyah; Muhammad Fakhri Hibatillah; Rihlah Nur Aulia (STKIP Pesisir Selatan, 2026)
Objective: This article examines how Islamic educational institutions in Indonesia, ranging from madrasah and integrated Islamic schools to pesantren, manage their curricula amid the demands of digital transformation, identifies the structural, cultural, and managerial challenges faced, and maps the learning innovations developed in response to these demands. Methods: A qualitative library research method was applied, in which forty-five scholarly sources, comprising journal articles, theses, and policy documents published between 2019 and 2025, were traced through Google Scholar, SINTA, and Garuda, then analysed thematically following the Miles and Huberman model, with source triangulation used to ensure validity. Results: Digital transformation opens opportunities such as administrative efficiency, flexible online learning, and expanded access to resources, but it is also confronted by four structural challenges: limited technological infrastructure, gaps in educators' digital competence, cultural resistance rooted in pesantren tradition, and the absence of a clear managerial framework that risks eroding Islamic values. Novelty: This study frames curriculum management as a single integrated process spanning planning, organising, implementation, and evaluation, and proposes a value-based curriculum management model as the foundation for sustainable digital transformation that safeguards the religious character of Islamic educational institutions.